2000
DOI: 10.1172/jci5250
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone links pituitary adrenocorticotropin gene expression and release during adrenal insufficiency

Abstract: IntroductionAdrenal glucocorticoid production is regulated by the complex integration of stimulatory and inhibitory signals that maintain homeostasis during stress (1-3). Secretion of adrenocorticotrophic hormone (ACTH) by the pituitary -the primary stimulus for glucocorticoid release -is modulated by the hypothalamic neuropeptides corticotropin-releasing hormone (CRH) and vasopressin (VP); the release of these neuropeptides is in turn influenced by inputs from other regions of the central nervous system (CNS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 41 publications
3
69
0
Order By: Relevance
“…The first such reported study (Smart & Low 2003) gave twice daily injections of 1µg of ACTH(1-24) to Pomc null mice but found that this treatment did not result in the restoration of adrenal function. To put this into perspective, the basal circulating levels of plasma ACTH in mice are in the 100 pg/mL range (Muglia et al 2000, Laurent et al 2002. A dose of 1µg could potentially achieve a theoretical maximum concentration in the animal of approximately 30 ng/mL (based on a 30 g body weight) or around 300 times basal levels.…”
Section: The Pomc -/-Mousementioning
confidence: 99%
“…The first such reported study (Smart & Low 2003) gave twice daily injections of 1µg of ACTH(1-24) to Pomc null mice but found that this treatment did not result in the restoration of adrenal function. To put this into perspective, the basal circulating levels of plasma ACTH in mice are in the 100 pg/mL range (Muglia et al 2000, Laurent et al 2002. A dose of 1µg could potentially achieve a theoretical maximum concentration in the animal of approximately 30 ng/mL (based on a 30 g body weight) or around 300 times basal levels.…”
Section: The Pomc -/-Mousementioning
confidence: 99%
“…This complexity challenges efforts to determine precisely how a single homeostatic challenge generates functional linkages among the afferents it recruits, the chemical signals these release, and the signaling programs initiated in CRH neuroendocrine neurons for peptide synthesis/secretion. Identifying these linkages is critical for understanding principles of signal specificity; perturbing these linkages may complicate obesity, diabetes, and/or stress-related disorders (Muglia et al, 2000;Inouye et al, 2002;Müller et al 2003;Balthasar et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that systemic glucocorticoids facilitate clearance of thymocytes destined to die by neglect or by negative selection [33]. The role of endogenous glucocorticoids in mediating inflammationinduced thymocyte apoptosis depends on the type of stimulus used.…”
Section: Introductionmentioning
confidence: 99%